Oedipus Complex Tokoh Tamura Kafka pada Novel Umibe no Kafuka Karya Murakami Haruki: Tinjauan Psikoseksual Sigmund Freud - I Kadek Antartika; Gede Satya Hermawan; Wiwit Cahyaningrum (Universitas Airlangga, 2025)
This study aims to describe the Oedipus Complex in the character Tamura Kafka in the novel